Zooplankton assemblages in two reservoirs: one subjected to accentuated water level fluctuations, the other with more stable water levels - Geraldes, Ana Maria (2008)
The abundance, composition and dynamics of zooplankton were followed in two reservoirs of the River Douro catchment. The Serra Serrada Reservoir is subject to marked fluctuations in water levels. The highest values of total phosphorus, soluble reactive phosphorus, nitrate, water colour and chlorophyll a were found during the minimum level phase. Rotifera was dominant except in late summer and autumn when the cladoceran Ceriodaphnia quadrangula or the copepod Tropocyclops prasinus replaced them as the dominant zooplankton. Among the rotifers the most common taxa were Keratella cochlearis, Conochilus sp. and Asplanchna priodonta. Maximum rotifer density was about 80,000 ind m–3 in 2000, 200,000 ind m–3 in 2001 and 100,000 ind m–3 in 2002. Among the crustacean zooplankton C. quadrangula achieved densities of up to 45,000 ind m–3 and T. prasinus, up to 80,000 ind m–3. Canonical correspondence analysis revealed a strong contribution of the variation in the stored water volume, temperature, total phosphorus, chlorophyll, nitrates, and water transparency to the observed, significant association between zooplankton assemblage and environmental variables. In the Azibo Reservoir, fluctuations in water level are smaller. Only total phosphorus, cholorophyll and conductivity varied seasonally. Cladocera and Copepoda were dominant during the whole study period. The most abundant taxa were Ceriodaphnia pulchella, Daphnia longispina, Diaphanosoma brachyurum, Bosmina longirostris and Copidodiaptomus numidicus. Cladocera achieved densities of up to 25,000 ind m–3 and Copepoda up to 15,000 ind m–3. Rotifera in general reached densities of up to 6,000 ind m–3. On the basis of canonical correspondence analysis only temperature and conductivity were significantly associated with zooplankton assemblage.